2019
DOI: 10.1097/01.ju.0000557396.48819.c3
|View full text |Cite
|
Sign up to set email alerts
|

Mp79-17 the Impact of Intraoperative Ketorolac on Overall Narcotic Requirements in Patients Undergoing Ureteroscopy: A Randomized, Controlled Trial

Abstract: fragmentation and dusting settings were measured (n[15). The retropulsion force was recorded both per pulse and per second at each setting. Laser fiber burn back was measured with the Begostone phantom in contact with the laser fiber tip. Two hundred micron fibers were utilized for the testing. RESULTS: The SPTF laser produced significantly less retropulsion compared to long pulse dusting and fragmentation settings of the 120W Holmium:YAG laser (p<0.001). Retropulsion of the Thulium fiber laser was similar whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…This is consistent with prior studies that have shown counseling to have a significant impact on postoperative pain control [16,17] . Intravenous ketorolac has been shown to reduce narcotic requirements in the PACU and after discharge [18] . Additionally, alpha blockers and oxybutynin, in combination and alone, have been shown to reduce symptoms related to ureteroscopy and ureteral stents [19,20] .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This is consistent with prior studies that have shown counseling to have a significant impact on postoperative pain control [16,17] . Intravenous ketorolac has been shown to reduce narcotic requirements in the PACU and after discharge [18] . Additionally, alpha blockers and oxybutynin, in combination and alone, have been shown to reduce symptoms related to ureteroscopy and ureteral stents [19,20] .…”
Section: Discussionsupporting
confidence: 85%
“…[ 16 , 17 ] Intravenous ketorolac has been shown to reduce narcotic requirements in the PACU and after discharge. [ 18 ] Additionally, alpha blockers and oxybutynin, in combination and alone, have been shown to reduce symptoms related to ureteroscopy and ureteral stents. [ 19 , 20 ] There exists many nonopioid based alternatives for pain control after ureteroscopy that can be combined for effective analgesia.…”
Section: Discussionmentioning
confidence: 99%